Sol-gel synthesis and characterization studies of NiMoO4 nanostructures for photocatalytic degradation of methylene blue dye - Thilagavathi, P. (American Scientific Publishers, 2016)
Nanostructured nickel molybdate (NiMoO4) nanoparticles (NPs) were successfully synthesized by using nickel nitrate and ammonium molybdate as the precursors and citric acid as the fuel by a simple modified sol-gel method. The prepared samples were characterized by powder X-ray diffraction (XRD), Fourier transform Infrared (FT-IR) spectra, high resolution scanning electron microscope (HR-SEM), energy dispersive X-ray (EDX), UV-Visible diffuse reflectance spectra (DRS), photoluminescence (PL) spectra and vibrating sample magnetometer (VSM) techniques. Powder XRD, FT-IR and EDX results were confirmed that the resultant powders was pure and single phase crystalline with monoclinic structure. HR-SEM images show that the morphology of the obtained powder consist nanostructued particles-like morphology. VSM results showed ferromagnetic behavior of the samples. Photo-catalytic activity of NiMoO4 NPs was tested for the photo-catalytic degradation (PCD) of methylene blue (MB) and it was found that higher PCD efficiency.